Highways and Wildlife: Problems and Solutions - Joe Schaefer; Frank J. Mazzotti; Craig Huegel (EDIS)
The expanding network of highways built to transport Florida's residents and visitors has a severe impact on our wildlife resources. Information on this topic is currently in great demand by conservationists, planners, and road builders. Increased knowledge of wildlife movements, use of habitat, and reactions to highways, in addition to greater experience with innovative roadway designs, offer opportunities to lessen the negative impacts of roads on native fauna. This fact sheet summarizes the known or suspected relationships between highways and wildlife in Florida, and solutions that may help to minimize problems. Readers are encouraged to consult the listed references for more information. This is document WEC-172, one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published:1993, as SS-WIS-41. Revised: February, 2003.